Determinants of Trade Deficit in Nepal: An Econometric Investigation - Nepal, Surendra Raj (Nepalese Journal of Statistics, 2020)
Background: Nepal has been importing some of goods and services from other countries and is also capable of exporting some other goods and services to foreign countries. Because of over dependency on foreign goods, Nepal has been suffering from trade deficit for more than 45 years. Objective: This study aims to investigate the relationship of trade deficit in Nepal with its determinants by using econometric analysis where exchange rate, real gross domestic product and foreign direct investment are taken as determinants of trade deficit. Its main objective is to examine the long-run, short-run and causal relationship among the variables. Materials and Methods: Annual time series data from 1974/75 (from 1988/89 in case of FDI) to 2018/2019 obtained from different sources: Nepal Rastra Bank, Economic Survey of Nepal, The World Bank and Department of Industry, Nepal Government were used in this study. Unit root test was used to check stationary. Autoregressive Distributed Lag (ARDL), ARDL bound test and Error Correction Model (ECM) were applied to find short-run as well as long-run relationship. Finally, pair-wise causal relationship was tested by using Granger causality. Results: All variables were found to be stationary at first difference. The test statistic of ARDL bound test was 8.17 and was greater than upper bound of 6.36 at 1% significance level. Error correction term’s p-value was 0.0052 and the corresponding values for pair-wise Granger causality from trade deficit to FDI and FDI to trade deficit were 0.00009 and 0.00005, respectively. Conclusion: There was positive and significant long-run relationship between exchange rate and trade deficit whereas there was negative and significant long-run relationship between real GDP and trade deficit. Moreover, real GDP positively affected trade deficit in short-run. Furthermore, bidirectional causal relationship has been observed between FDI and trade deficit.